Time to clinical stability among children hospitalized with pneumonia. Issue 6 (28th April 2015) - Wolf, Rachel B.; Edwards, Kathryn; Grijalva, Carlos G.; Self, Wesley H.; Zhu, Yuwei; Chappell, James; Bramley, Anna M.; Jain, Seema; Williams, Derek J.
<x xml:space="preserve">Abstract</x> We evaluated the performance of time to clinical stability (TCS), a longitudinal outcome measure using 4 physiologic parameters (temperature, heart rate, respiratory rate, and use of supplemental oxygen), among children enrolled in a prospective study of pneumonia hospitalizations. We calculated the time from admission to normalization for each of the 4 parameters individually along with various combinations of these parameters (≥2 parameters). We assessed for agreement between the combined TCS measures and both hospital length of stay and an ordinal severity scale (nonsevere, severe, and very severe). Overall, 323 (96.7%) of 334 included children had ≥1 parameter abnormal on admission; 70 (21%) children had ≥1 parameter abnormal at discharge. For the 4 combined measures, median TCS decreased with increasing age. Increasing TCS was associated with both longer length of stay and increasing disease severity. The simplest combined measure incorporating only respiratory rate and need for supplemental oxygen performed similarly to more complex measures including additional parameters. Our study demonstrates that longitudinal TCS measures may be useful in children with pneumonia, both in clinical settings to assess recovery and readiness for discharge, and as an outcome measure in research and quality assessments. Additional study is needed to further validate our findings. Journal of Hospital Medicine 2015;10:380–383. © 2015 Society of Hospital Medicine